SCHOOL ATTITUDE AND ACADEMIC PERFORMANCE OF STUDENTS FROM A RELOCATION AREA IN CAVITE: BASIS FOR A PLANNED SCHOOL/CLASSROOM MOTIVATIONAL ACTIVITIES - Mark Anthony Tangan (MultiTech Publisher, 2023)
This descriptive study was conducted to determine the relationship between school attitude of students from a relocation area in Cavite and their academic performance in order to devise a school/classroom motivation activity. The study was based on the concept interpreted by Godwin and Okoronka (2015) of the Congruity Theory. The questionnaire used was adopted in the SAAS-R- School Attitude Assessment Survey-Revised developed by McCoach and Siegle (2013) as the means of gathering the data. The questionnaire was composed of 35 items which were divided into 5 dimensions namely: (a) Academic Self-Perception, (b) Attitude toward Teachers and Classes, (c) Attitude toward School, (d) Goal Valuation, (e) Motivation and Self-Regulation. The respondents of the study were 122 students residing from a relocation area in Cavite, and their 15 teachers. Twenty percent of the students were randomly interviewed while answering the questionnaire. t-test and F-test or one-way ANOVA were used to test the significant differences in school attitude of students according their demographic profile. Pearson Product Moment Correlation were also used to test the significant relationship between school attitude of students and their academic performance. The profile of the students shows that most of the respondents are 12-14 years old. There are more female respondents than male. The respondents are from 3 grade levels. Most of the respondents are from Grade 7 followed by Grade 8, and Grade 9. Their family income is below Php 6,000.00 to Php 10,000.00 which is lower than the poverty line of Php 9,000.00 monthly income. As for their parents’ educational attainment most of them are college level. Findings reveal that only students school attitude under dimension Goal Valuation are rated strongly agree and the other dimensions namely: Attitude toward Teachers and Classes, Attitude toward School, and Motivation and Self-Regulation are rated agree. Academic Self-Perception is rated slightly agree. The comparison of school attitude to the demographic profile reveals that the overall attitude is significantly different in terms of gender. There is significant relationship only between Goal Valuation and Academic Performance in Araling Panlipunan. This study recommends that the attitude of the respondents should be sustained particularly towards teachers and classes, attitude towards school, goal valuation, motivation and self-regulation. Improvement on academic self-perception is needed to build stronger self-belief that they are intelligent and smart. In addition, conducting remedial classes and peer tutoring to the respondents is necessary to improve academic performance. Implementation of the Planned Classroom/School Motivation Activities is recommended. This study is recommended as reference for the future researchers for further studies involving more students from different relocation areas.